Walkthrough Analysis by the Green Areas of Encosta Norte Housing Complex, Itaim Paulista, São Paulo - Paula, Franklin Roberto Ferreira de; Imbronito, Maria Isabel (National Journal of City Management, 2023)
This article aims to explore the green areas of the Encosta Norte Housing Complex, located in the Itaim Paulista district, East Zone 2 of the city of São Paulo, in order to figure out how the local community perceives those spaces from the identification of existing weaknesses and potentialities, as well as to recall the indications of wishes for improvements in its extensions. In addition to the technical field visits to the territory, some activities with the residents and other local agents were proposed as a methodology for the construction of this cartography. The methodological instrument applied to the population was the walkthrough analysis, or route-interview, that took place on 09/17/2022, aiming to record, through notes, audio recordings and photographs, the perceptions of the community about the inhabited place. The achieved results demonstrate that the participants of the activity relate to the place through affective memories of how the territory used to be, just before the urbanization process that began to be implemented in the mid-1980s. Some problems such as lack of maintenance of open spaces and springs and water courses were also pointed out as weaknesses. The researchers, proponents of the dynamics, reinforce the potential of transforming these available public areas belonging to CDHU as a strategy for the requalification of the area and for the improvement of the quality of life of local population.